‘Culture’ in Finnish migrant-background youth’s discourses constructing togetherness and distance - Kimanen, Anuleena; Tigert, Johanna; Alisaari, Jenni; Khalili, Samaneh (Taylor & Francis, 2025)
'Culture' as a construct has a complex role in the position of youth with migration background in Europe. It has been used to stereotyping and othering them, but recognising diverse cultural heritages positively affirms their identities. However, migrant-background youth's discourses concerning culture have not sufficiently been investigated. Based on two interview datasets, we analyse how youth with migration background construct their identities and negotiate togetherness with and distance from others through the concept of culture. The discourse analysis paid attention to the linguistic, discursive and social practices. As a linguistic practice, the participants talked about separate 'cultures' when describing similarity with other youth with migration background and distance between them and the 'Finns'. As a discursive practice, 'cultures' were defined as shared norms or communication styles but also similar mindsets. The accounts of intercultural learning brought up the significance of culture in validating migrant-background youth's identity. As a social practice, the notion of culture constructed 'Finns' and 'foreigners' as distinctive groups with certain power imbalance. Schools should deliberately deconstruct the essentialising notion of culture to help youth with migration background find more nuanced explanations to their experiences of togetherness or distance, question the power imbalances and cross inter-group barriers.